Numerical Simulation Study of Hydraulic Fracturing Nozzle Erosion in Deep Well - Xu, Yuqiang; Li, Qiandeng; Li, Bingshuo; Guan, Zhichuan (Frontiers in Physics, 2022)
Hydraulic jet fracturing technology is one of the main means to develop low permeability and deep reservoirs. However, due to the large displacement and high sand ratio in the construction process, the erosion wear of high-speed sand particles on the hydraulic jet fracturing nozzle is more serious, which reduces the erosion cutting ability of the nozzle. Therefore, based on Finnie principle, a three-dimensional model of nozzle is established to analyze the influence of internal multiphase flow field distribution, flow rate, sand volume fraction, sand diameter and nozzle outlet size on nozzle erosion. The results show that the erosion velocity increases nonlinearly with the increase of inlet pressure. With the increase of erosion time, the erosion rate gradually tends to be stable; with the increase of fluid viscosity, the erosion rate decreases; with the increase of the diameter and mass flow rate of the erosion particles, the erosion speed also increases, indicating that the size and mass flow rate of the erosion particles are the main factors affecting the erosion effect of the nozzle. The research results have important guiding significance for the rational use of the tool and the extension of the service life of the tool.